1991
DOI: 10.1155/1991/57017
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation After Cholecystectomy. TheRole of the Cystic Duct Stump

Abstract: The so-called “Postcholecystectomy Syndrome” may be due to various pathological biliary causes. The aim of this study was to evaluate the significance of the cystic duct stump syndrome and if so, how often a long (>1.5 cm) cystic duct stump was an indication for reoperation on the bile ducts after cholecystectomy in our patients. Three hundred and twenty two patients underwent a second operation on the bile ducts after cholecystectomy in the last ten years. In 35 patients (10.8%) a striking finding was a long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 8 publications
0
43
1
1
Order By: Relevance
“…It could be concluded that the presence of a long cystic duct stump or a gallbladder remnant (With or without calculi) on investigation, in patients with persistent post-cholecystectomy symptoms definitely demands surgical intervention, especially when a stone is present. [1,[9][10][11][12] We could not come across any reports about the outcomes of conservative management of patients with postcholecystectomy remnant and persistent symptoms. One of our patients was managed with completion cholecystectomy after clearance of CBD calculi by ERCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be concluded that the presence of a long cystic duct stump or a gallbladder remnant (With or without calculi) on investigation, in patients with persistent post-cholecystectomy symptoms definitely demands surgical intervention, especially when a stone is present. [1,[9][10][11][12] We could not come across any reports about the outcomes of conservative management of patients with postcholecystectomy remnant and persistent symptoms. One of our patients was managed with completion cholecystectomy after clearance of CBD calculi by ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…1,[10][11][12][13][14] These patients can remain asymptomatic, 1,13,14 or they can present with acute symptoms (biliary colic, acute cholecystitis or acute pancreatitis) or chronic symptoms (persistent right upper quadrant discomfort or pain, food intolerance, nausea or jaundice). 1,[8][9][10][11][12][13][14] Although there are no pathognomic symptoms, the persistence of symptoms after cholecystectomy should alert the clinician to the possibility of a gallbladder remnant, especially when coupled with radiation of pain to the shoulder, food intolerance, nausea or jaundice. 1,15 Similarly, the timing of presentation is also very variable, with patients presenting at any time between less than 1 year and up to 25 years after cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear from the existing literature as to what is the natural history of these gallbladder remnants over a period of time, but there seems to be a trend towards surgical intervention in symptomatic patients. It could be concluded that the presence of a long cystic duct stump or a gallbladder remnant (with or without calculi) on investigation, in patients with persistent post-cholecystectomy symptoms definitely demands surgical intervention, especially when a stone is present [13,14,15] . Patients with gall bladder remnant can be asymptomatic or they can present with acute symptoms (biliary colic, acute cholecystitis or acute pancreatitis) or chronic symptoms (persistent right upper quadrant discomfort or pain, food intolerance, nausea or jaundice) [16] .…”
Section: Imaging Anatomymentioning
confidence: 99%
“…The presentation of a gallbladder remnant can be variable not only in terms of clinical features, but also in relation to the time interval after cholecystectomy. 1,[10][11][12][13][14] These patients can remain asymptomatic, 1,13,14 or they can present with acute symptoms (biliary colic, acute cholecystitis or acute pancreatitis)…”
Section: 9-12mentioning
confidence: 99%
“…1,[8][9][10][11][12][13][14] Although there are no pathognomic symptoms, the persistence of symptoms after cholecystectomy should alert the clinician to the possibility of a gallbladder remnant, especially when coupled with radiation of pain to the shoulder, food intolerance, nausea or jaundice. 1,15 Similarly, the timing of presentation is also very variable, with patients presenting at any time between less than 1 year and upto 25 years after cholecystectomy.…”
Section: 9-12mentioning
confidence: 99%